Contemporary office-based procedures in rhinology: a narrative review of techniques, indications, and outcomes - Alokby, Ghassan (Frontiers in Allergy, 2025)
BackgroundThe role of office-based procedures in rhinology has expanded considerably, driven by advancements in minimally invasive techniques and a growing emphasis on value-based care. These interventions can offer effective management for selected sinonasal conditions while reducing reliance on operating room resources.ObjectiveTo provide a comprehensive narrative review of contemporary office-based rhinologic procedures, focusing on indications, anesthetic considerations, patient selection, and safety protocols. Additionally, to share institutional experience, highlighting practical benefits in workflow optimization and patient access.MethodsA narrative review was conducted by searching PubMed, Embase, and Scopus databases for English-language articles published between [2010–2025] using the keywords: office-based rhinology, balloon sinuplasty, cryotherapy, radiofrequency neurolysis, nasal valve collapse, and Eustachian tube dilation. Priority was given to clinical studies, systematic reviews, and guidelines relevant to procedural safety, efficacy, and healthcare resource utilization. Additionally, institutional data from King Faisal Specialist Hospital and Research Centre (KFSHRC) were reviewed to illustrate real-world application.ResultsThe review highlights key office-based procedures, their indications, contraindications, anesthetic strategies, and safety considerations. Institutional experience demonstrated a 140% increase in office-based procedures over two years, reduced waiting times, and improved operating room efficiency, particularly for routine turbinate surgeries.ConclusionOffice-based rhinologic procedures offer safe, effective, and resource-efficient alternatives for selected patients. While current evidence and institutional experiences are promising, further research is warranted to standardize practice, evaluate long-term outcomes, and assess economic impacts across healthcare systems.